2019
DOI: 10.1177/1120672119830861
|View full text |Cite
|
Sign up to set email alerts
|

Needle revision outcomes after glaucoma filtering surgery: survival analysis and predictive factors

Abstract: Purpose: To evaluate the efficacy and safety of needle revision and examine factors predictive of failure. Methods: In total, 157 eyes of 131 patients that underwent needle revision augmented with either 5-fluorouracil or betamethasone for trabeculectomy failure were included in this retrospective study. Complete failure was defined as additional glaucoma surgery, ciliodestructive procedures, loss of light perception, sight-threatening complications, hypotony maculopathy, and surgical bleb revision. Success wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…According to the literature, this type of adverse event has been described after classic filtration surgery (trabeculectomy), no mention of minimally invasive glaucoma surgery devices or of bleb filtering surgery has been referred. 15 In our case, needling revision after a PreserFlo MicroShunt implantation caused heavy bleeding in the anterior chamber from a filtering bleb, with an IOP rise. The condition improved slowly and resolved within 14 days after.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…According to the literature, this type of adverse event has been described after classic filtration surgery (trabeculectomy), no mention of minimally invasive glaucoma surgery devices or of bleb filtering surgery has been referred. 15 In our case, needling revision after a PreserFlo MicroShunt implantation caused heavy bleeding in the anterior chamber from a filtering bleb, with an IOP rise. The condition improved slowly and resolved within 14 days after.…”
Section: Discussionmentioning
confidence: 61%
“…Most reports describe cases of hyphema after needling in patients who underwent trabeculectomy, nevertheless the site of the anterior chamber bleeding is not specified. According to the literature, this type of adverse event has been described after classic filtration surgery (trabeculectomy), no mention of minimally invasive glaucoma surgery devices or of bleb filtering surgery has been referred 15…”
Section: Discussionmentioning
confidence: 99%
“…Helosa A. et al reported that there was no significant difference in preoperative corneal endothelial cell density at 12 months [18]. However, several studies indicated that the subconjunctival injection of antimetabolites can cause severe damage to corneal endothelial cells [26][27][28][29]. While such complications are rare, they cannot be resolved through observation or treatment with ocular instillation and may require corneal transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…ROCK inhibitors were reported to have the potential to improve corneal endothelial diseases, such as Fuchs endothelial dystrophy or corneal edema, and to have a protective effect on corneal endothelial cells after cataract surgery [ 30 , 31 , 32 , 33 , 34 ]. The exact mechanism by which ROCK inhibitors improve corneal endothelial cells has not been fully elucidated, but it is possible that these promote the reactivation of cell proliferation and migration, and the restoration of the corneal endothelial pump and barrier functions, contributing to the regeneration of corneal endothelial cells [ 29 , 35 ]. In this study, there was no change in corneal endothelial cell density more than 12 weeks after the needling surgery.…”
Section: Discussionmentioning
confidence: 99%
“…As in any bleb-forming procedure, [19][20][21] postoperative management may be required to optimize its function. In line with our BN rate of 30%, recent publications have reported approximately 30%-40% postoperative needling rates in both retrospective 9,10 and prospective 12,22 studies but it can be as high as 62% of BN when more than one needling is performed in the same eye.…”
Section: Discussionmentioning
confidence: 99%